Learning philosophical thinking through collaborative writing in secondary education - Corcelles Seuba, Mariona; Castelló, Montserrat (Journal of Writing Research, 2015)
This study investigated students’ practice of philosophical thinking through collaborative writing in secondary education. A philosophy course was developed following the rationale of the learning communities in which writing was used as an epistemic tool. 45 students organized into 13 teams participated in the course. In this study, a subsample of six students working in 2 teams during one collaborative argumentative writing activity were analyzed. These groups were selected on the basis of their output (high and medium quality) and because both followed an integrating construction strategy for collaborative writing. Data collected included audio, video and computer screen recordings of both groups’ discourse and writing activity during collaborative writing (using Camtasia and Atlas-ti software). Analysis focused on collaborative writing interaction (types of talk; evidence of philosophical competences - problematization, argumentation and conceptualization; regulation of the collaborative writing activity and group dynamics) and the quality of individual and collaborative texts. Results indicate that quality of the interaction was related to text quality. Collaborative writing helped the students: 1) to transform abstract ideas into more concrete and appropriate philosophical concepts using examples related to their experiences, 2) to use these philosophical concepts in their own discourse and 3) to problematize their own ideas and provide arguments to support them. From these results, the importance of a structured context of learning to promote critical thinking through writing is discussed as well as the need to train students to develop efficient peer discussion for learning through collaborative writing.